Finnish regional policy in transition: towards rigid planning machine or dynamic governance? - SOTARAUTA, Markku (European Spatial Research and Policy, 1997)
In regional policy, the fierce global economic competition stresses the need to create new kinds of interactions between public sector and business aimed at discovering other ways of generating new innovations. The dynamics of contemporary changes have not only challenged us to find new strategies, but to find new ways to organise policy making. This article describes the Finnish programme-based regional policy and scrutinises such critical points as: development programmes and innovations, the guidance of development programmes, collective action and control. The mai n contribution is presented in the form of postulates.